Construção e validação de um instrumento para avaliação da integralidade do cuidado odontológico na atenção primária, sob a perspectiva do cirurgião-dentista - Grazielle Christine Maciel Mattos (2014)
Objectives: To develop and validate a questionnaire instrument to assess primary health care from the perspective of dentists, based on key concepts related to comprehensiveness of care. Moreover, to identify the perception of these professionals regarding comprehensiveness and its key concepts. Methods: A 46-item instrument was developed using literature review and focus group discussions on concepts of comprehensiveness based on the published literature across the three domains of patient welcoming, bonding and quality of care. The developed questionnaire was analysed to determine the potential for item reduction in order to create an integrated and robust instrument. Content and face validity were tested by a panel of experts, followed by a pilot testing with two samples of primary care dentists resulted in minor modifications to the wording of questions. Construct validity was tested on a reference population of 207 tenured dentists working in primary care within the public sector in the city of Belo Horizonte through a sequence of statistical tests comprising exploratory factor analysis and reliability tests. Data were analysed using SPSS version 20. It has also carried out a description of the perception of the professionals about the studied domains by calculating proportions. Results: The focus group discussions confirmed the importance of the three domains to explore the concept of comprehensiveness in primary care. In the instrument, eight of the 46 items showed poor performance in more than a half of the statistical tests and they were removed. The item reduction analyses resulted in a 38-item questionnaire and the exploratory factor analysis presented a final ten-factor model supported by the initial scree plot grouping of items. The majority of items loaded > 0.4 on factors 1 to 10 and the model accounted for 61 per cent of the variance. The reduced scale, with 38 items, improved the construct, both Kaiser-Meyer-Olkin test (KMO) and Cronbachs alpha coefficient increased from 0.59 and 0.679 to 0.62 and 0.76 respectively. In most items (79.0%), professionals perceptions about the comprehensiveness were overwhelmingly positive. When the analysis was stratified by domain, it was found that the items in that perception was less favorable were in the quality of care domain (12.5 %), followed by the patient welcoming (22.7%) and the bonding (25.0%). Conclusions: Overall, the instrument shows good evidence of reliability and construct validity. Further research and testing of this instrument are discussed for future work. Comprehensiveness, as an approach in health care practice, needs to be enhanced, and there is evidence that these dentists are aware of its importance.